Retrospective data of Neuroendocrine Cancer diagnosed in Hospital Universiti Sains Malaysia / Siti Aisyah Ibrahim - Ibrahim, Siti Aisyah (2014)
The aim of the present study was to investigate the incidence of Neuroendocrine Tumour Cases in Hospital USM and compared to other report. This study was done to analyse the statistic of previous data in HUSM Kelantan whether there is similarity with other study in the world. The incidence of neuroendocrine tumour is reported to be 2.5 to 5 per 100000 per year compared with 1.09 per 100,000 in 1973 and prevalence of 35 per 100,000. The incidence of the neuroendocrine tumour is increasing in the US population from 1983 to 2013, which is increase from 1.7 to 7.8 per 100000 incidences. In my study, the data of Neuroendocrine Tumours diagnosed in HUSM is 48. The most frequent site diagnosed with Neuroendocrine Tumour is gastrointestinal tract (27.1%) and it is support by Taal et al (2004) with the percentage of the gastrointestinal tract was 62-67%. NETs can be clinically symptomatic (functioning) or silent (nonfunctioning). The incidence of Neuroendocrine Tumour in Hospital USM was higher in female (68.8%) compare to male (31.3%). But the result reported was different with the other study. Niederle, M., B., et al (2010) reported that male higher than female.